Diet of the Two-banded Plover at Caleta Valdes, Peninsula Valdes, Argentina - D'amico, Veronica Laura (2004)
The diet of the Two-banded Plover Charadrius falklandicus was studied during the non-breeding season, March–May 2000, by means of an analysis of 49 droppings collected on the beach at Caleta Valdés, Península Valdés, Argentina. From invertebrate sampling, three potential prey types were identified: polychaetes, insects and crabs. The polychaete Laeonereis acuta occurred most frequently in the droppings and this was also the most abundant invertebrate in the substrate of the beach. The average biomass of L. acuta in each of the 40 droppings that contained any was 8.9 mgAFDM. This suggests that the Two-banded Plovers feeding on this prey consume 1.77 individuals per minute or an intake rate for L. acuta alone of 0.26 mgAFDM/s based on the average defecation rate.